Alpha-SNAP (M105I) mutation promotes neuronal differentiation of neural stem/progenitor cells through overactivation of AMPK - Bustamante-Barrientos, Felipe A.; Méndez-Ruette, Maxs; Molina, Luis; Koning, Tania; Ehrenfeld, Pamela; González, Carlos B.; Wyneken, Ursula; Henzi, Roberto; Bátiz, Luis Federico (Frontiers in Cell and Developmental Biology, 2023)
Background: The M105I point mutation in α-SNAP (Soluble N-ethylmaleimide-sensitive factor attachment protein-alpha) leads in mice to a complex phenotype known as hyh (hydrocephalus with hop gait), characterized by cortical malformation and hydrocephalus, among other neuropathological features. Studies performed by our laboratory and others support that the hyh phenotype is triggered by a primary alteration in embryonic neural stem/progenitor cells (NSPCs) that leads to a disruption of the ventricular and subventricular zones (VZ/SVZ) during the neurogenic period. Besides the canonical role of α-SNAP in SNARE-mediated intracellular membrane fusion dynamics, it also negatively modulates AMP-activated protein kinase (AMPK) activity. AMPK is a conserved metabolic sensor associated with the proliferation/differentiation balance in NSPCs. Methods: Brain samples from hyh mutant mice (hydrocephalus with hop gait) (B6C3Fe-a/a-Napahyh/J) were analyzed by light microscopy, immunofluorescence, and Western blot at different developmental stages. In addition, NSPCs derived from WT and hyh mutant mice were cultured as neurospheres for in vitro characterization and pharmacological assays. BrdU labeling was used to assess proliferative activity in situ and in vitro. Pharmacological modulation of AMPK was performed using Compound C (AMPK inhibitor) and AICAR (AMPK activator). Results: α-SNAP was preferentially expressed in the brain, showing variations in the levels of α-SNAP protein in different brain regions and developmental stages. NSPCs from hyh mice (hyh-NSPCs) displayed reduced levels of α-SNAP and increased levels of phosphorylated AMPKα (pAMPKαThr172), which were associated with a reduction in their proliferative activity and a preferential commitment with the neuronal lineage. Interestingly, pharmacological inhibition of AMPK in hyh-NSPCs increased proliferative activity and completely abolished the increased generation of neurons. Conversely, AICAR-mediated activation of AMPK in WT-NSPCs reduced proliferation and boosted neuronal differentiation. Discussion: Our findings support that α-SNAP regulates AMPK signaling in NSPCs, further modulating their neurogenic capacity. The naturally occurring M105I mutation of α-SNAP provokes an AMPK overactivation in NSPCs, thus connecting the α-SNAP/AMPK axis with the etiopathogenesis and neuropathology of the hyh phenotype.